Percepción de la imagen corporal y hábitos alimenticios en adolescentes de un colegio vespertino de la ciudad de Loja - Minga Minga, Jhaely Fernanda (2023)
In the adolescent stage, the perception of body image has a crucial influence sincea series of physical, emotional, social and cognitive changes are manifested, during this stage they experience concern for their physical appearance, generating possible inadequate eating behaviors. Therefore, the general objective of this research is to determine the relationship between the perception of body image and eating habits in adolescents of an evening school in the city of Loja. The methodology used had a quantitative approach, with a non-experimental design because the variables were not manipulated, in addition, a cross-sectional and descriptive correlational study, with a sample of 103 adolescents between 13 and 18 years old. The instruments used for data collection were the Body Shape Questionnaire (BSQ) and the Adolescent Food Habits Checklist (AFHC). In the results regarding the perception of body image, the prevalenceof the level of "no concern about body shape" is significantly evident. Likewise, in eatinghabits, "healthy eating habits" stands out. Therefore, these results indicate that obtaininghealthy eating habits is a predictor to show higher levels of body satisfaction, however, this factor is not totally determinant, this is proven by the application of Spearman's correlation coefficient where a very significant, low and positive relationship between both variables was evidenced, therefore, these results obtained allowed the elaboration ofthe mental health promotion plan focused on body satisfaction and potentiation of healthyeating habits in adolescents with a psycho-educational and cognitive-behavioral approach